Risk assessment for fire and explosion accidents of steel oil tanks using improved AHP based on FTA. Issue 3 (31st October 2015) - Zhang, Miao; Song, Wenhua; Chen, Zhen; Wang, Ji
Abstract : The fire and explosion accidents of steel oil tanks is an extreme threat for crude oil storage, and they are considerably difficult to extinguish and easy to spread. Fault Tree Analysis (FTA) and Analytic Hierarchy Process (AHP) are often used for the risk assessment of such accidents. The probabilities of basic events are very different to obtain. For example, the failure probabilities of most components in industrial are related to their service time, work environment, operating, and some probabilities of human factors are more difficult to establish. So, there are no sufficient data for FTA to make accurate quantitative assessments, whereas the AHP relies on expert judgment and scoring, which have great subjectivity. Both the structural importance of the basic events for FTA and the weight of the index layer for the AHP significantly affect the top event. A new approach is proposed to improve the AHP method. The judgment matrices of AHP are developed based on the basic events, structural importance of FTA, and the expert scoring of AHP. In addition, the new method reconciles the differences of FTA and AHP by combining the weighting factors, and has been tested and validated by applying for fire and explosion accidents of different types of steel oil tanks. Finally, the risk of boilover fire in tank park and its influencing factors are discussed. The results provide valuable information for the decision maker to improve the safety performance and to set up an effective firefighting strategy. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 260–269, 2016